Rola bibliotek cyfrowych w badaniach regionalnych - Marcinkowski, Piotr (Biuletyn Historii Wychowania, 2008)
The article presents the questions concerning digital libraries. The aims for their establishment have been discussed and the most interesting Polish examples presented. The author, on the basis of the selected collections highlights the role the digital libraries may play in the workshop of a researcher - regionalist. Moreover, he demonstrates their significance as a tool supporting didactic process. From among several dozen o f Polish virtual libraries, the author focuses especially on Wielkopolska Biblioteka Cyfrowa (Great Polish Digital Library) and Kujawsko-Pomorska Biblioteka Cyfrowa (Kujavian-Pomeranian Digital Library) as the biggest and most interesting projects of this kind.